Benefits and Pitfalls of Debunking Interventions to Counter mRNA Vaccination Misinformation During the COVID-19 Pandemic. Issue 5 (October 2022) - Schmid, Philipp; Betsch, Cornelia
Misinformation about mRNA vaccination is a barrier in the global fight against the COVID-19 pandemic. Thus, authorities often rely on text-based refutations as a countermeasure. In two experiments ( N = 2, 444), text-based refutations effectively reduced the belief in misinformation and immunized participants against the impact of a misleading social media post. However, a follow-up ( N = 817) questions the longevity of these debunking and prebunking effects. Moreover, the studies reveal potential pitfalls by showing a row of unintended effects of the refutations (lacking effect on intentions, backfire-effects among religious groups, and biased judgments when omitting information about vaccine side effects).